Interrogating Gazes Comparative Critical Views on the Representation of Foreignness and Otherness - Gifra-Adroher, Pere; Gifra-Adroher, Pere; Hambrook, Glyn; Cots, Montserrat (Peter Lang, 2013)
This book focuses on the theme of foreignness and its representation in literature and cognate discourses. The volume brings together essays in English, Spanish and Catalan that consider from original and informed perspectives both the conceptualization of the foreign and foreignness in its human, geographical/spatial, historical and cultural guises, not only as contemplated but also as a lens in the act of contemplation. This multi- and inter-disciplinary collection of essays is the result of an inspired and timely collaboration between specialists in comparative literature from across the world. Dealing with fundamental questions relating to the trans- and intercultural, otherness, migration, cosmopolitanism and the global, it will be of interest to researchers and students in comparative literature, modern languages and area studies, travel writing, intercultural studies, sociolinguistics and social anthropology.